Approved estimates of the Government of Yobe State of Nigeria 1993 - Government of Yobe State of Nigeria (Yobe, Nigeria : Yobe State Nigeria, 1993)
This volume provides the details of approved estimates of the Government of Yobe State of Nigeria 1992
aia 19/02/2019
Loans
Keywords: Budget; Expenditures, public; Nigeria